2023
DOI: 10.3390/genes14020256
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Phylogenetic Analysis of Casein Gene Family in Camelus ferus

Abstract: Camel milk is known for its exceptional medical uses. It has been used since ancient times to treat infant diarrhea, hepatitis, insulin-dependent diabetes (IDDM), lactose intolerance, alcohol-induced liver damage, allergies, and autism. It has the power to treat several diseases, with cancer being the most significant. This study investigated the evolutionary relationship, physiochemical characteristics, and comparative genomic analysis of the casein gene family (CSN1S1, CSN2, CSN1S2, and CSN3) in Camelus feru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Only a few SNPs (4 out of 18 in Bactrian and 2 out of 16 in dromedary) were found in the retrotransposons, contributing to 17.6% of the total genetic diversity found. This result reflects a lower level of genetic diversity found in the casein genes of camelids [3,14,[18][19][20]22,23,61,62] compared to ruminants [13,[63][64][65][66]. These findings are consistent with the observations made by other authors, indicating a significant reduction in genetic diversity due to at least two bottlenecks during the history of camel domestication [56,67,68].…”
Section: Discussionsupporting
confidence: 91%
“…Only a few SNPs (4 out of 18 in Bactrian and 2 out of 16 in dromedary) were found in the retrotransposons, contributing to 17.6% of the total genetic diversity found. This result reflects a lower level of genetic diversity found in the casein genes of camelids [3,14,[18][19][20]22,23,61,62] compared to ruminants [13,[63][64][65][66]. These findings are consistent with the observations made by other authors, indicating a significant reduction in genetic diversity due to at least two bottlenecks during the history of camel domestication [56,67,68].…”
Section: Discussionsupporting
confidence: 91%
“…Casein is a unique protein in milk . CSN2 is a member of the casein family . We found that almost all isolated cells could express CSN2, indicating that the isolated cells had lactation function.…”
Section: Discussionmentioning
confidence: 73%
“…29 CSN2 is a member of the casein family. 30 We found that almost all isolated cells could express CSN2, indicating that the isolated cells had lactation function. In summary, the cells we isolated could be used for subsequent research.…”
Section: Functional Prediction Of Mir-200amentioning
confidence: 70%
“…Few isolated studies have been there for unconventional species. A phylogenetic study of different casein proteins of Camelus ferus depicted distinct clusters of different proteins (Parveen et al, 2023) [6] . Comparative genomic analysis provides a better insight on overall functionality and antimicrobial nature of abundant milk protein casein.…”
Section: Introductionmentioning
confidence: 99%